Integrated passive microwave and unmanned aerial vehicle studies of Hudson Bay sea ice during the summer melt period - Harasyn, Madison Leigh (2019)
Inaccuracies in sea ice observations from passive microwave satellite sensors increase during the summer melt period due to the evolution of sea ice thermophysical properties driving complexity in ice emissivity. Research from this thesis examines variations in sea ice thermophysical properties in Hudson Bay throughout summer melt and relates them to ice surface emissivity. This is achieved through the collection and analysis of a time-series of in situ passive microwave and unmanned aerial vehicle measurements of sea ice. Contributions from this thesis are made under two overarching categories: 1) the influence of sediment presence on sea ice passive microwave signature and; 2) the evolution of in situ and satellite-based sea ice emissivity throughout the melt period in Hudson Bay. Results from this research link non-uniform distribution of sediment across the ice surface to increased surface topography, as a result of enhanced melt rates from decreased surface albedo. The in situ passive microwave signature of sediment-laden ice is then examined, in relation to the surface roughness and liquid water presence on the ice surface. This thesis also verifies the evolution of in situ sea ice emissivity during the melt period in relation to the existing literature, and distinct periods of ice emissivity during ice melt are highlighted. In situ and satellite-based microwave brightness temperatures are compared, facilitated by a multi-sensor approach. To the authors' knowledge, these results contribute the first multi-sensor in situ observations of sediment laden sea ice, and the first comprehensive analysis of the emissive properties of Hudson Bay sea ice throughout the summer melt period. October 2019